STUDY THE EFFECT OF SHOT PEENING RESIDUAL STRESSES ON COMPRESSIVE STRENGTH OF STIFFENED PANEL - ZHANG ZiPeng; LIU Cun; YIN KaiJun (Jixie qiangdu)
To determine the effects of shot peening on stiffened panel compressive strength,a typical shot peening residual stress was introduced by ABAQUS subroutine. Then,using temperature field equivalent method to transfer residual stress distribution to temperature boundary conditions. The local buckling and post-buckling characteristics of stiffened panels with different residual stress peak value and residual compressive stress depth are calculated respectively. The results show that,the influence coefficient of shot peening relate to the peak value of residual stress and the range of compressive stress depth. A simple determination method for influence coefficient of shot peening is given and the functions in engineering are amended. In the end,the residual stress distribution of a group of test specimens were obtained through shot peening simulation,the accuracy of amended method was verified by comparison of compression tests of shot specimens and unshot specimens.